Congenital anomalies of the kidney and the urinary tract: A murmansk county birth registry study. Issue 3 (2nd February 2016) - Postoev, Vitaly A.; Grjibovski, Andrej M.; Kovalenko, Anton A.; Anda, Erik Eik; Nieboer, Evert; Odland, Jon Øyvind
Abstract : BACKGROUND: Congenital anomalies of the kidney and the urinary tract (CAKUTs) are relatively common birth defects. The combined prevalence in Europe was 3.3 per 1000 in 2012. The risk factors for these anomalies are not clearly identified. The aims of our study were to calculate the birth prevalences of urinary malformations in Murmansk County during 2006 to 2011 and to investigate related prenatal risk factors. METHODS: The Murmansk County Birth Registry was the primary source of information and our study included 50, 936 singletons in the examination of structure, prevalence and proportional distribution of CAKUTs. The multivariate analyses of risk factors involved 39, 322 newborns. RESULTS: The prevalence of CAKUTs was 4.0 per 1000 newborns (95% confidence interval [CI], 3.4–4.5) and did not change during the study period. The most prevalent malformation was congenital hydronephrosis (14.2% of all cases). Diabetes mellitus or gestational diabetes (odds ratio [OR] = 4.77; 95% CI, 1.16–19.65), acute infections while pregnant (OR = 1.83; 95% CI, 1.14–2.94), the use of medication during pregnancy (OR = 2.03; 95% CI, 1.44–2.82), and conception during the summer (OR = 1.75; 95% CI 1.15–2.66) were significantly associated with higher risk of CAKUTs. CONCLUSION: The overall fourfold enhancement of the occurrence of urinary malformations in Murmansk County for the 2006 to 2011 period showed little annual dependence. During pregnancy, use of medications, infections, pre‐existing diabetes mellitus, or gestational diabetes were associated with increased risk of these anomalies, as was conception during summer. Our findings have direct applications in improving prenatal care in Murmansk County and establishing targets for prenatal screening and women's consultations. Birth Defects Research (Part A) 106:185–193, 2016. © 2016 Wiley Periodicals, Inc.